POTENSI WANA WISATA ALAM BATU KUDA UJUNGBERUNG BANDUNG - Marini Eko Putri; Nova Eviana (Panorama Nusantara, 2015)
Batu Kuda natural ecotourism has a viable tourism potency for supporting economic financial resources for local government and community. Some efforts are needed to develop its potencies in accordance with its typical characteristics. This research aims to identify the potencies of Batu Kuda tourist attractions using 5A’s theory, covering the aspects of access, accommodation, attraction, activity, and amenity. They are then elaborated and analyzed with SWOT analytic method consisting of strength, weakness, opportunity, and threat aspects. Observation and interview are conducted to collect research data. The result of research shows that internal and external factors of Batu Kuda tourist attraction is on first quadrant, referring to the aggressive strategy. It means that the growth oriented strategy is needed to develop the potency.